Propofol Related Infusion Syndrome: Ultrastructural Evidence for a Mitochondrial Disorder. Issue 1 (January 2018) - Vollmer, Jörg-Peter; Haen, Susanne; Wolburg, Hartwig; Lehmann, Rainer; Steiner, Jochen; Reddersen, Silke; Fend, Falko; Fallier-Becker, Petra
Abstract : Objective: The objective of this report of a fatal propofol-related infusion syndrome in a young adult was to present—to our knowledge for the first time—direct ultrastructural evidence for the central role of mitochondrial damage in the pathogenesis of this syndrome. Data Sources: Histological and electron microscopical analysis of liver, skeletal, and heart muscle obtained by autopsy and blood obtained from patient. Study Selection: Case report. Data Extraction: In addition to conventional macroscopical and histological investigations, electron-microscopical analysis of myocardial- and skeletal muscle and liver tissue obtained at autopsy from a young man was performed in order to search for ultrastructural changes of mitochondria. Acylcarnitine concentrations of his blood were determined by ultra-high performance liquid chromatography mass spectrometry. Data Synthesis: A 19-year-old male was admitted with acute left-side hemiparesis. The patient was intubated, then propofol infusion started, and a craniotomy was performed to remove an intracerebral hematoma. In the postoperative period, the patient presented with elevated intracranial pressure and brain edema. After repeat surgery, the patient showed impaired systolic left ventricular function, increasing fever, anuria, hyperkalemia, and metabolic acidosis, and he finally expired. Electron microscopy revealed dark, electron dense amorphous structures associated with mitochondria in heart muscle and liver tissue obtained at autopsy. Peripheral blood analysis revealed increased levels of acetyl-, propionyl-, butyryl-, malonyl-, and valeryl-carnitine as an indicator for propofol-related infusion syndrome, as well as for propofol-mediated inhibition of free fatty acid uptake into mitochondria, affecting beta-oxidation. Conclusions: Electron dense bodies found in association with mitochondria in muscle and liver cells probably correspond to accumulation of free fatty acid provide direct morphological evidence for the mitochondrial damage in propofol-related infusion syndrome.